Danish ethics council rejects brain death as the criterion of death – commentary 2: return to Elsinore. Issue 1 (March 1990) - Pallis, Christopher
Abstract : No discussion of when an individual is dead is meaningful in the absence of a definition of death. If human death is defined as the irreversible loss of the capacity for consciousness combined with the irreversible loss of the capacity to breathe spontaneously (and hence to maintain a spontaneous heart beat) the death of the brainstem will be seen to be the necessary and sufficient condition for the death of the individual. Such a definition of death is not something radically new. It is merely the reformulation – in the language of the neurophysiologist – of much older concepts such as the 'departure of the (conscious) soul from the body' and the 'loss of the breath of life'. All death – in this perspective – is, and always has been, brainstem death....